Multi-level regulation of even-skipped stripes by the ubiquitous factor Zelda. - Bishop, T.R.; Onal, P.; Xu, Z.; Zheng, M.; Gunasinghe, H.; Nien, C.Y.; Small, S.; Datta, R.R. (Development, 2023)
The zinc-finger protein Zelda (Zld) is a key activator of zygotic transcription in early Drosophila embryos. Here, we study Zld-dependent regulation of the seven-striped pattern of the pair-rule gene even-skipped (eve). Individual stripes are regulated by discrete enhancers that respond to broadly distributed activators; stripe boundaries are formed by localized repressors encoded by the gap genes. The strongest effects of Zld are on stripes 2, 3 and 7, which are regulated by two enhancers in a 3.8 kb genomic fragment that includes the eve basal promoter. We show that Zld facilitates binding of the activator Bicoid and the gap repressors to this fragment, consistent with its proposed role as a pioneer protein. To test whether the effects of Zld are direct, we mutated all canonical Zld sites in the 3.8 kb fragment, which reduced expression but failed to phenocopy the abolishment of stripes caused by removing Zld in trans. We show that Zld also indirectly regulates the eve stripes by establishing specific gap gene expression boundaries, which provides the embryonic spacing required for proper stripe activation.